2017
DOI: 10.1097/md.0000000000007312
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cytokines can help to identify the development of severe acute pancreatitis on admission

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
2
22
1
Order By: Relevance
“…These results were consistent with those of previous studies showing that WBC count, NLR, CRP, BUN, and creatinine were associated with the severity of acute pancreatitis. [4510111524] The above serum biomarkers showed a significant difference also in the logistic regression analysis of this study. In contrast, previous studies related to AST and total bilirubin were not found.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These results were consistent with those of previous studies showing that WBC count, NLR, CRP, BUN, and creatinine were associated with the severity of acute pancreatitis. [4510111524] The above serum biomarkers showed a significant difference also in the logistic regression analysis of this study. In contrast, previous studies related to AST and total bilirubin were not found.…”
Section: Discussionsupporting
confidence: 60%
“…[11] In addition, there are reports of albumin, total cholesterol, high-density lipoprotein, creatinine, and cytokines being able to predict severe acute pancreatitis. [12131415] However, these serum markers also had their limitations and no definitive consensus as to the prognostic criteria for acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of PTX3 was significantly higher only in patients with severe acute pancreatitis, and it was considered an independent prognostic factor in the course of the disease. The concentration of PTX3 reached a maximum concentration earlier than CRP and reached similar values in the early stage of the disease to the concentration of IL-6 [24]. In our tested group of patients with AP, the concentration of PTX 3 in the first 24 h of the disease was four times higher in mild AP and seven times higher in SAP, in comparison with the control group.…”
supporting
confidence: 62%
“…The aim of this study was to further elucidate the role of PTX3 as a diagnostic and prognostic marker in acute pancreatitis (AP), a potentially strong inflammatory disease, and compare it to CRP. The role of PTX3 as a predictor of severity in AP has previously been studied in AP, with conflicting results 810 . Furthermore, a formal link between PTX3, SIRS and disease severity of AP has not yet been established.…”
Section: Introductionmentioning
confidence: 99%